Evaluation of Diuretic Activity of Isatin Derivatives in Wistar Rats - E. Venkateshwarlu; B.S. Sharvana Bhava; K. Umasankar; J. Venkateshwar Rao (Journal of Pharmacy and Nutrition Sciences, 2013)
In the present studies we have synthesized ten derivatives of novel isatin-3-[N2-(2-benzalaminothiazol-4-yl)]hydrazone and characterized by the help of physical and spectral data. The selected male Wistar albino rats were divided into different groups: control, urea (1 g/kg), furosemide (5 mg/kg), of isatin derivatives (Ia-Ij, 10 and 100 mg/kg) treated groups. All the drugs were administered orally and animals were pretreated with normal saline (25 ml/kg) before start the experiment. The urine volume (in ml) and content of Na+, K+ & Cl were measured in the urine of rats at 5th hour. The volume of urine output increased significantly (p<0.05) in urea, furosemide and also isatin derivatives treated groups when compared with control groups. The diuretic activity of isatin derivatives were exhibited moderated to less when compared with furosemide. The diuretic response with its electrolyte of the isatin derivatives was highly remarkable in comparison with control group. Based on the results the isatin derivatives show hypernatremic, hypercholermic and hyperkalemic diuretics as conventional diuretics (furosemide).